Insufficient antenatal identification of fetal growth restriction leading to intrauterine fetal death: a regional population-based study in Japan - Tokoro, Shinsuke; Koshida, Shigeki; Tsuji, Shunichiro; Katsura, Daisuke; Ono, Tetsuo; Murakami, Takashi; Takahashi, Kentaro (The journal of maternal-fetal & neonatal medicine, 2023)
Fetal growth restriction (FGR) is associated with perinatal adverse outcomes including intrauterine fetal death. Antenatally unidentified FGR has a higher risk of intrauterine fetal death than that identified antenatally. We, therefore, investigated the antenatal identification of FGR among intrauterine fetal deaths, and assessed the perinatal factors associated with the identification of FGR. This retrospective and population-based study reviewed all stillbirths in Shiga Prefecture, Japan, from 2007 to 2016 with exclusion criteria of multiple births, births at unidentified gestational weeks or < 22 gestational weeks, and lethal disorders. We analyzed cases of FGR, using the Japanese clinical definition: Z-score of estimated fetal weight for gestational age <−1.5 standard deviations (SD). We identified 94 stillbirths with FGR among 429 stillbirths. Thirty-seven cases were antenatally identified during pregnancy management (39%). Dividing cases by a Z-score of −2.5 SD, 51 cases were classified as ≤−2.5 SD. Twenty-eight of the 51 cases (55%) with a Z-score <−2.5 SD were antenatally identified as having FGR, whereas 9 of the 43 cases (21%) with a Z-score ≥−2.5 SD were antenatally identified as having FGR (p = .002). Among cases with a Z-Score <−2.5 SD, 16 of 21 (76%) beyond 28 weeks' gestation and 12 of 30 (40%) before 28weeks' gestation were antenatally identified as having FGR (p = .023). Fetal growth restriction leading to intrauterine fetal death in Japan was antenatally identified in less than half of cases. Antenatal identification of FGR was associated with the severity of growth restriction.